If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + -9 = 2y + 15 Reorder the terms: -9 + -6y = 2y + 15 Reorder the terms: -9 + -6y = 15 + 2y Solving -9 + -6y = 15 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -9 + -6y + -2y = 15 + 2y + -2y Combine like terms: -6y + -2y = -8y -9 + -8y = 15 + 2y + -2y Combine like terms: 2y + -2y = 0 -9 + -8y = 15 + 0 -9 + -8y = 15 Add '9' to each side of the equation. -9 + 9 + -8y = 15 + 9 Combine like terms: -9 + 9 = 0 0 + -8y = 15 + 9 -8y = 15 + 9 Combine like terms: 15 + 9 = 24 -8y = 24 Divide each side by '-8'. y = -3 Simplifying y = -3
| 4y-12=y-12 | | x+2y-3z=9 | | X+24+2x=-19-2x-22 | | -9w=-12 | | -2a+8+6a=9a-3a | | 5a=-2 | | 18x^3-27x= | | 52+5y-21=17y-14-3y | | 3x+4/2x+3=x+14/x+8 | | 20=-6a | | x+3/x+1=x-3/x-8 | | -7r=6 | | 4z-15-z+3=0 | | 62-5x=10x+18 | | -6x=9 | | 4d=8-4d | | 4r=-4 | | 9/x+5=15/x+3 | | -(5a+8)+2(a+7)=-4a-5a | | (5x+1)3=15x+3 | | 6x+8/x-2=8 | | m,7-25=-19 | | 3i+3=10-4i | | 4x+4/2=6 | | 2a^2+12a=0 | | 4x+59=10+11 | | 4f=12 | | 20=5a | | 5x(5x-7)(9x+5)=0 | | 3x-9/3=8 | | -8=2b | | -33=-11t |